Project Management Competencies for Master Students: Curriculum Development in Two Romanian Universities - Lucian Belascu (European Scientific Journal, ESJ, 2016)
The Bologna Process has as one of its main pillars the link between academic curricula and labour market requirements. This process has built a space for dialogue and cooperation which reaches far beyondEurope, where the basic values of the European society – freedom of expression and research, free movements of academics and students, students active participation to learning and tolerance – have been put at the forefront of education. Since 1999, Romanian universities have tried to adjust their curricula and academic offers for study programs to the requirements of the labour market, sometimes with some reluctance from the various partners involved in this process. As the field of Project Management has gained more standing on the Romanian labour market, the need for graduates skilled in Project Management increased, thus leading to the need of providing students enrolled in master programs in Economics, but with different specializations, courses and topics in Project Management. The paper outlines the experience of adapting the curriculum of master programs in Economics in two renowned Romanian universities – Bucharest University of Economic Studies and Lucian Blaga University of Sibiu - to Project management needs, within a project implemented with the support of the European Social Fund for Human Resources Development (POSDRU). The paper presents the most important curriculum changes implemented for the master programs under analysis and explains the importance of these changes.